The organizational response to social problems - Schutt, Russell K.; Hartwell, Stephanie W. (Amsterdam ; New York : JAI Press, 2001)
From the de-institutionalization of psychiatric hospitals to the privatization of prisons, the dramatic public policy changes of the last three decades have been, to a large extent, changes in organization. The chapters in this volume examine these organizational changes. We learn how organizations shift strategies, create alliances, cross boundaries and react to incentives as they respond to changing environmental pressures. We learn about the complex relationships between organizations and their clients and how these relations can be altered in response to environmental change. Chapters in the first section focus primarily on inter-organizational relations among health care and community development organizations. Chapters in the second section focus primarily on relations between organizations and their clients, both in medical organizations and in the criminal justice system.
The organizational response to social problems : changing interorganizational and organization-client relations / Russell K. Schutt and Stephanie W. Hartwell -- Beyond Babel : establishing system-wide principles of collaborative care for adults with serious and persistent mental illness / Larry Davidson ... [et al.] -- Community-based service providers for people with chronic care needs : survival in an uncertain environment / Mary L. Fennell, Susan M. Allen and Linda Laliberte -- The government non-profit relationship : towards a partnership model for HIV/AIDS prevention in the Latino community / Maria Elena Letona and Carole C. Upshur -- Implementing a mental health case management system : technological change and organizational structure / Russell K. Schutt -- Ritual conformity to the Americans with Disabilities Act : coercive and normative isomorphism / Teresa L. Scheid and Mark C. Suchman -- Organizational infrastructure and community capacity : the role of broker organizations / Robert J. Chaskin -- Fighting drug and alcohol abuse in communities and improving race relations : theoretical lessons learned / Benjamin P. Bowser, K. Deborah Whittle, and David Rosenbloom -- Between partnership and privatism : the case of Rebuild L.A. / Dennis J. Downey -- Organizing a community response to environmental injustice : Walpole Island's Heritage Centre as a social movement organization / Robert Van Wynsberghe -- Toward an understanding of responses to methadone maintenance treatment organizational style / Margaret S. Kelley -- The sexual culture of psychiatric treatment facilities and mental illness clients' HIV risk : a theoretical framework and pilot study / Eric R. Wright -- Resource mobilization and the reduction of prison violence / Matthew Silberman -- A public health--juvenile justice collaboration to address the psychiatric needs of incarcerated youth / Robert McMackin and Carl Fulwiler -- Child abuse and its consequences / Calvin J. Larson.
Includes bibliographical references.
Description based on print version record.
Keywords: Social problems -- United States; Organizational behavior -- United States; Community organization -- United States; Social theory; Organizational theory & behaviour; Political Science -- Public Policy -- Social Services & Welfare; United States -- Social conditions